Ethics and Brain Death in Pediatrics: Recent Controversy and Practical Suggestions - Bibler, Trevor M.; Galbraith, Kyle L.; Brothers, Kyle B. (Journal of Pediatric Intensive Care, 2017)
Who decides when a child is dead? The story of Jahi McMath has brought this question into focus for pediatric intensivists, ethicists, and the American public. In this article, we address this question by arguing that medical professionals do not have an obligation to acquiesce when families insist upon postmortem therapies. To do so may harm the dignity of the child by subjecting him or her to procedures that objectify the body, damage the child's reputation, and violate his or her privacy. Applying this answer to the real world of pediatric intensive care, we suggest practices meant to preserve the dignity of the child while accepting that the family is struggling to understand the tragedy. Muddled communication or an unyielding attitude will fail to help the family understand and cope with the death of their young loved one. Clear and honest communication—in conjunction with an empathetic disposition—can improve pre- and postmortem care for both patient and family.
Keywords: brain death; irreversible coma; pediatrics; ethics; grief; empathy; person; suffering